Monocyte recruitment in venous thrombus resolution. - Ali, T; Humphries, J; Burnand, K; Sawyer, B; Bursill, C; Channon, K; Greaves, D; Rollins, B; Charo, I; Smith, A (2006)
OBJECTIVE: To investigate the importance of monocyte recruitment in thrombus resolution and the role of cysteine-cysteine (CC) chemokines and the CC chemokine receptor, CCR2, in this process. METHODS: Peritoneal macrophages, monocyte chemotactic protein 1 (MCP1), or carrier solutions were injected into thrombi induced in the vena cava of rats. Caval thrombi were also formed in CCR2-/- and MCP1-/- mice and in wild-type mice transfected with an adenoviral construct expressing a broad-spectrum CC receptor antagonist. RESULTS: Direct administration of peritoneal macrophages decreased thrombus size by more than fivefold and increased recanalization by more than fourfold compared with controls (P < .001). A 100-ng MCP1dose reduced thrombus size by more than sixfold (P < .01) and increased recanalization by more than sevenfold (P < .01), without affecting macrophage recruitment. Deletion of CCR2 or blockade of all CC chemokines inhibited both monocyte recruitment (P < .05) and thrombus resolution (P < .01), but knocking out MCP-1 had no effect. CONCLUSION: Increasing macrophage numbers in the thrombus enhances its resolution. MCP1 treatment enhances resolution by stimulating recanalization, independent of an effect on monocyte recruitment. CCR2 deficiency has the same effect as blockade of all CC chemokines. CCR2 receptor activation may therefore be an important mechanism in monocyte recruitment into venous thrombi and could be targeted to promote their resolution.